Clinico-epidemiological profile of fever of unknown origin in an Egyptian setting: A hospital-based study (2009–2010) - Ahmed F Kabapy; Amira M Kotkat; Hanan Zakaria Shatat; Ekram W Abd El Wahab (Journal of Infection in Developing Countries)
Introduction: Fever of unknown origin (FUO) is one of the most challenging diagnostic dilemmas in the field of infectious diseases and tropical medicine. Clinicians should use the frequency distribution of disorders causing FUO to guide their diagnostic approach in patients with prolonged, unexplained fevers meeting the definition of FUO. Methodology: The present study was undertaken to examine the etiologies, clinico-epidemiologic profile, and prognosis of classical FUO in patients reporting to the Alexandria Fever Hospital in Egypt. Records of 979 patients admitted to the fever hospital (from January 2009 to January 2010) and diagnosed as having FUO were examined carefully. FUO was defined as three outpatient visits or three days in the hospital without elucidation of cause of fever. Results: A total of 979 cases (57.0% males and 43.0% females), with ages ranging from 0.2 to 90 years, were investigated. The mean duration of fever before hospitalization was 31 ± 10 days. The etiology of FUO was delineated in 97% of cases, and only 3% remained undiagnosed. Diagnoses were grouped into five major categories. Infectious causes of FUO were strongly associated with better outcome (73.7% improved). Smoking, contact with animals or birds, drug addiction, and HIV seropositivity were important risk factors associated with infections. Conclusions: Infections are the most common cause of FUO, followed by collagen vascular diseases, in our region. A three-step diagnostic work-up approach is recommended to be applied in Egypt in order to improve the quality of medical service provided to FUO patients.